CE-FPN: enhancing channel information for object detection - Luo, Yihao; Cao, Xiang; Zhang, Juntao; Guo, Jingjuan; Shen, Haibo; Wang, Tianjiang; Feng, Qi (Multimedia tools and applications, 2022)
Feature pyramid network (FPN) has been an efficient framework to extract multi-scale features in object detection. However, current FPN-based methods mostly suffer from the intrinsic flaw of channel reduction, which brings about the loss of semantical information. And the miscellaneous feature maps may cause serious aliasing effects. In this paper, we present a novel channel enhancement feature pyramid network (CE-FPN) to alleviate these problems. Specifically, inspired by sub-pixel convolution, we propose sub-pixel skip fusion (SSF) to perform both channel enhancement and upsampling. Instead of the original 1 × 1 convolution and linear upsampling, it mitigates the information loss due to channel reduction. Then we propose sub-pixel context enhancement (SCE) for extracting stronger feature representations, which is superior to other context methods due to the utilization of rich channel information by sub-pixel convolution. Furthermore, we introduce a channel attention guided module (CAG) to optimize the final integrated features on each level. It alleviates the aliasing effect only with a few computational burdens. We evaluate our approaches on Pascal VOC and MS COCO benchmark. Extensive experiments show that CE-FPN achieves competitive performance and is more lightweight compared to state-of-the-art FPN-based detectors.